Understanding the experience of chronic pain: a latent profile analysis of chronic pain in relation to general health - Beck, Austin Ray (Kansas State University, 2018)
Chronic pain is one of the most pervasive healthcare conditions being treated today. The onset of chronic pain can start at any age, and can follow a myriad of trajectories. Health conditions like chronic pain have been shown to be associated with increases in depression, anxiety, and other adverse mental health outcomes. The present study utilized a sample of 10,266 adult individuals with chronic conditions where chronic pain was typically present to identify different profiles of chronic pain sufferers and then examine the associations between general health, chronic pain profile membership, and mental health outcomes. Although previous studies have attempted to identify chronic pain profiles, no study has yet explored how pain frequency and intensity, fatigue, duration of chronic condition, and physical limitations caused by this condition may uniquely identify subgroups within the chronic pain population. Utilizing a latent profile analysis, four distinct profiles of chronic pain were identified, including a Constant Companion profile, an Adjustments Needed profile, an Annoying Companion profile, and a No Limitations profile. Through a path analysis, significant associations were found between both general health and changes in general health, chronic pain profile membership, and frequency of anxious, depressed, and hopeless feelings. Results generally were counterintuitive, with better health linked with higher odds of fitting the more extreme chronic pain profiles compared to the no limitations profile; and those in the more extreme chronic pain profiles had significantly less frequent feelings of depression, anxiety, and hopelessness. Ideas for clinical implications and suggestions for future research are provided.
Keywords: Chronic pain; Depression; Anxiety; Mental health; General health